2016
DOI: 10.3390/molecules22010004
|View full text |Cite
|
Sign up to set email alerts
|

Development and Structural Modification of BACE1 Inhibitors

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder which usually occurs in the elderly. The accumulation of β-amyloid and the formation of neurofibrillary tangles are considered as the main pathogenies of AD. Research suggests that β-secretase 1 (BACE1) plays an important role in the formation of β-amyloid. Discovery of new BACE1 inhibitors has become a significant method to slow down the progression of AD or even cure this kind of disease. This review summarizes the different types and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Sufficient target engagement to neuronal BACE1 has been much concerned in the development of BACE1 inhibitors to minimize plaque pathology. As the catalytic core of the enzyme is relatively wide, early generations of BACE1 inhibitory compounds are too large to have sufficient brain penetration [ 149 , 151 ]. With chemical modification of lead compounds, brain permeable BACE1 inhibitors have been successfully developed, with several front-running candidates in the pipeline entered clinical trials.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient target engagement to neuronal BACE1 has been much concerned in the development of BACE1 inhibitors to minimize plaque pathology. As the catalytic core of the enzyme is relatively wide, early generations of BACE1 inhibitory compounds are too large to have sufficient brain penetration [ 149 , 151 ]. With chemical modification of lead compounds, brain permeable BACE1 inhibitors have been successfully developed, with several front-running candidates in the pipeline entered clinical trials.…”
Section: Main Textmentioning
confidence: 99%
“…In the pharmaceutical industry, there are examples that opportunity and success of drug discovery arise from initially unspeculated therapeutic target or effect of the candidate drugs (as was the case of Viagra). As mentioned earlier, during the development of BACE1 inhibitors many lead compounds are discarded from further translational evaluation because they are not brain penetrant to target neuronal BACE1 [ 149 ]. The discussions elaborated above would imply that brain impermeable inhibitors could otherwise serve as desired anti-CAA drug candidates.…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, due to the large size of catalytic domain that hinders the design of potent small inhibitors, some important structural features should be taken into consideration to enhance the binding affinity within key residues of the binding pocket, particularly the catalytic aspartic dyad [9,10]. Interactions with Tyr71, Thr72, and Gln73 (flap region), among other residues (Gly11, Gly34, Gly230, Thr231, Thr232, and Arg235) have also been reported as crucial for the inhibition activity of a wide variety of scaffolds of small BACE1 inhibitors that have been developed in the last years [11]. Experimental data have also shown that the cellular trafficking of BACE1 involves different subcellular acidic compartments at the endosomal system, suggesting that its subcellular distribution is also a key determinant of its activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the formative stages of the Aβ peptide is mediated by the specific enzyme β secretase enzyme (β‐site amyloid precursor protein cleaving enzyme 1, BACE1; Saido, ). Several efforts have been made to design and synthesize BACE1 inhibitors, but none of them have reached the pharmacological market yet (Ghosh, Cárdenas, & Osswald, ; Gu et al., ). Besides, the obtention of new, more active, and selective BACE1 inhibitors in this an area would (a) lower the costs of AD therapy and (b) prevent possible failures in the clinical phases of the inhibitors, currently in their research stages.…”
Section: Introductionmentioning
confidence: 99%